(untitled) (Communications in Mathematical Research, 2021)
In this paper, we present some important generalizations of the Banach contraction principle, in which the Lipschitz constant k is replaced by some real-valued control function. For the applications to the fractal space, we obtain the fixed point theorem of the some generalized contraction in the space of fractals.